O gênero Erythroxylum P. Browne (Erythroxylaceae) do Estado do Paraná, Brasil - Mendonça, Joalice De Oliveira [UNESP]; Cervi, Armando Carlos; Guimarães, Olavo Araújo (FapUNIFESP (SciELO), 1998)
An inventory of the Erythroxylum's species from the State of Paraná, Brazil, was done and the following species were found: E. ambiguum Peyr., E. amplifolium (Mart.) O.E. Schulz, E. anguifugum Mart., E. argentinum O.E. Schulz, E. buxus Peyr., E. campestre A. St.-Hil., E. cuneifolium (Mart.) O.E. Schulz, E. cuspidifolium Mart., E. deciduum A. St.-Hil., E. gonocladum (Mart.) O.E. Schulz, E. nanum A. St.-Hil., E. pelleterianum A. St.-Hil., E. microphyllum A. St.-Hil., E. myrsinites Mart, and E. suberosum A. St.-Hil.. All of then are taxonomically revised and a new synonym is presented: E. cuneifolium (Mart.) O.E. Schulz var. squarrosum O.E. Schulz as synonym of E. cuneifolium (Mart.) O.E. Schulz. Is also discussed the validity of the genus name Erythroxylon Linnaeus against Erythroxylum P. Browne. © 1998, Paraná Institute of Technology Publication.
Keywords: Erythroxylaceae; Erythroxylum; Flora; Paraná; Taxonomy